2012
DOI: 10.1186/1471-2458-12-974
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and survival in non-hereditary amyloidosis in Sweden

Abstract: BackgroundAmyloidosis is a heterogeneous disease caused by deposition of amyloid fibrils in organs and thereby interfering with physiological functions. Hardly any incidence data are available and most survival data are limited to specialist clinics.MethodsAmyloidosis patients were identified from the Swedish Hospital Discharge and Outpatients Registers from years 2001 through 2008.ResultsThe incidence of non-hereditary amyloidosis in 949 patients was 8.29 per million person-years and the diagnostic age with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
65
1
5

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(77 citation statements)
references
References 24 publications
3
65
1
5
Order By: Relevance
“…1 In the study on the general population living in Olmsted County from 1950 to 1989, the authors found an incidence rate of 9 cases per million person-years, and deduced that ;2200 new cases of AL amyloidosis are diagnosed in the United States annually. Incidence rates found in our analyses are slightly higher than those found in England and Sweden, 11,12 likely due to the fact that these 2 studies used older data and awareness of AL amyloidosis may have increased recently.…”
Section: Discussioncontrasting
confidence: 48%
See 2 more Smart Citations
“…1 In the study on the general population living in Olmsted County from 1950 to 1989, the authors found an incidence rate of 9 cases per million person-years, and deduced that ;2200 new cases of AL amyloidosis are diagnosed in the United States annually. Incidence rates found in our analyses are slightly higher than those found in England and Sweden, 11,12 likely due to the fact that these 2 studies used older data and awareness of AL amyloidosis may have increased recently.…”
Section: Discussioncontrasting
confidence: 48%
“…1 Other studies, although not population-based, have been conducted in European regions. For example, in 2 separate studies, Pinney et al 11 and Hemminki et al 12 estimated AL amyloidosis incidence rates to be ;3 and 8.3 cases per million person-years in 2008 in England and Sweden, respectively. Therefore, the literature suggests an estimated incidence between 3 and 12 cases per million persons per year, and an estimated prevalence of 30 000 to 45 000 AL amyloidosis patients in the United States and the European Union.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Akse-Onal and colleagues (6) A Swedish study identifying patients from hospital discharge and outpatient registers between 2001 and 2008 estimated an incidence of AA amyloidosis of 0.2 per 100 000, based on RA death rates (7). In 2013 an epidemiological study of systemic amyloidosis in England was conducted using combined data from the United Kingdom (UK) National Amyloidosis Centre (NAC) patient database and English death certificate data from the Office of National Statistics (8).…”
mentioning
confidence: 99%
“…22 In Amyloidosis a recent Swedish study, the estimated incidence of AL amyloidosis was 3.2 per million per year and AA amyloidosis 2.0 per million per year. 23 The median age for AL and AA amyloidosis is between 55 and 60 years. 24 The prognosis of untreated patients is poor, as noticed in older studies; median survival was 6 to 12 months for AL amyloidosis and 3 to 4 years for AA amyloidosis.…”
Section: Epidemiologymentioning
confidence: 99%